Exploring the Impact of Employee Satisfaction on Organizational Success: Evidence from Private Sector Organizations in Khost, Afghanistan - Jahan; Lalzai, Faridullah; Amin, Hafizullah Meen (Journal for Research in Applied Sciences and Biotechnology, 2023)
The primary objective of this research paper is to examine workplace employee satisfaction and its influence on the effective utilization of organizational resources. This entails exploring the various factors that significantly impact employee satisfaction within an organization, with the goal of identifying key drivers that have a profound effect on the morale and motivation of the workforce. By understanding these crucial factors, organizations can employ diverse strategies to enhance employee performance, thereby maximizing both individual and organizational objectives. In today's competitive market landscape, human resources are undeniably a critical asset for any organization. With intense competition, businesses are relentlessly striving to enhance customer satisfaction to gain a competitive edge. The utilization of human resources has a direct and substantial impact not only on customer satisfaction but also on gaining a competitive advantage. Consequently, it is imperative for managers to consistently assess employee satisfaction and pay close attention to the variables that exert significant influence on both employee satisfaction and performance. To investigate employee satisfaction and its ramifications on employee performance, this study employs a survey method. The utilization of an experimental approach is deemed unnecessary for this research, as employee satisfaction primarily involves theoretical aspects, making experimental methodologies redundant. Data for this research was collected through questionnaires, constituting primary data, targeting managers at various organizational levels within the private sector. The analysis of the gathered data reveals a robust positive correlation between employee satisfaction and employee performance. Notably, the variables most closely associated with employee satisfaction, and subsequently, with a significant impact on employee performance, are employee creativity and reduced absenteeism. Consequently, it can be confidently asserted that there exists a strong, positive relationship between employee satisfaction, employee performance, and the attainment of organizational goals.